DESAIN OPTIMUM CAMPURAN HOT ROLLED ASPHALT DENGAN MENGGUNAKAN PENDEKATAN ANALITIS - Santosa, Yanuar
Abstract: Since 1983 computer program DAMA has been used to analyze a multi-layered elastic pavement structure by cummulative damage techniques for a single or dual wheel load system. In this research, program DAMA was used to assess the optimum Hot Rolled Asphalt mixes resulting from the Marshall Test. The proposed surface layer thicknesses were 100, 200, 300 and 400 mm and the mixture was Hot Rolled Asphalt. One of the most important characteristics of Hot Rolled Asphalt is that the aggregate is gap graded. From Marshall test, it was found that increasing in compaction blows, i.e from 35, 50, 75 to 100 blows, increased the marshall stability, but reduced the void in mineral aggregates. It was also apparent that optimum binder content reduces with the increase in the number of compaction blows. Comparing the Marshall test results and the result from program DAMA, it was found that the optimum binder content from the Marshall test is fixed for a certain type and composition of the mix. On the other hand, the optimum binder content according to program DAMA is dependent on the structural number of pavement as well as on the number of compaction blows. It was also found that pavements with the same structural number but different in thickness composition appeared to required different optimum binder content and consequently the expected design life is also different. Further analysis on speciments compacted with 2 times 75 blows as an example, found that varying bitumen content by 10% around the optimum binder content will reduce the expected design life by 11% and 62% respectively for 10% more and 10% less bitumen contents. In line with those results obtained from the analytical approach that a longer design life could be resulted from the reduction in the void in mineral aggregates, the permanent deformation from wheel tracking test also tended to decrease. On the contrary, tests on marshall immersion for mixes with reduced binder content according to program DAMA appeared to be inconsistent. For 75-blow specimen, the result of indexes retained strength increase from 96.28% to 96.6%. And for 100-blos specimens, the result of the indexes retained strength decrease from 93.70% to 83.40%.